IMPLEMENTASI DAN TANTANGAN PENGELOLAAN BARANG MILIK NEGARA DI KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN C SUMBAWA - Reny Wardiningsih; Dwiyana Ramadhani; Rini Adriani Auliana (Jurnal Aplikasi Perpajakan, 2026)
State-Owned Asset (Barang Milik Negara/BMN) management is a crucial component of public financial governance, as it supports the implementation of institutional duties and functions while optimizing the utilization of state assets. This study aims to analyze the implementation of BMN management and identify the challenges faced at the Customs and Excise Supervision and Service Office (KPPBC) Type Madya Pabean C Sumbawa. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that BMN management has been implemented in accordance with the established management cycle, including planning, procurement, utilization, maintenance, administration, as well as supervision and control. The use of information systems such as SIMAN and SAKTI has contributed to improving data accuracy, transparency, and accountability in asset management. However, several challenges remain, including the existence of idle assets, unauthorized use of assets by external parties, and discrepancies between physical assets and recorded data. These findings suggest that although BMN management has been properly implemented, it has not yet been fully optimized, particularly in terms of asset utilization and supervision. Therefore, improvement efforts are required through strengthening internal controls, optimizing asset utilization, and enhancing data management systems to improve the overall effectiveness and accountability of BMN management.